ABUSE RELATED POSTS REPORTER USING WEB CRAWLER IN PYTHON - Dr. P .A. Tijare; Dishil Purswani; Tanishk Rathi; Swapnil Chavhan; Vijay Jangid; Shubham Agrawal (EPRA International Journal of Research and Development (IJRD), 2022)
This research paper shows one of the application areas where Web Scraping can be used to solve some social issues. According to [4], Web Scraping automates this process and helps you display all the data at the same place with ease and in a small amount of time. Main objective of Web Scraping is to extract information from one or many websites and process it into simple structures such as spreadsheets, database or CSV file. In our website, we have made use of this technology to solve a important social issue. Many cases of abuse have been increased with the use of Internet. Our website allows the authorized communities to search for such abuse related posts from different websites, while staying on a single webpage. The user will just have to enter the keyword, for e.g. – women abuse, and he will get the posts from several number of websites on a single webpage. The method explained in this paper is applied to a popular social platform – ‘Twitter’ as a use case. It can be applied to a number of websites. This will help the authorities to save time in searching for such crimes and give more time to solve these issues.